A method for preparing color-changing shed film

By combining manganese sulfate treatment with montmorillonite and organically modified hydrotalcite, a color-changing dimming shed film was prepared, which solved the problem of single dimming performance of the shed film, improved the weather resistance and dimming performance of the film, was suitable for different temperature and humidity environments, and promoted crop growth.

CN119613783BActive Publication Date: 2025-04-08SHANDONG SENBOSITE PLASTIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510162016.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-08
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

In the prior art, the dimming performance of the shed film is single, and the scattered light effect cannot be changed with time and temperature changes, resulting in the temperature in the shed being too high or too low, affecting crop growth.

Method used

Montmorillonite is treated as the raw material for the inner layer material, and combined with the addition of organically modified hydrotalcite insulating masterbatches, a color-changing dimming shed film is prepared to improve the weather resistance and dimming performance of the film.

Benefits of technology

It is achieved to improve the weather resistance of the film, especially the retention rate of nominal strain of fracture, appropriately reduce the transpiration of plants, and improve the photosynthesis rate of crops while ensuring the dimming performance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a method for preparing a color-changing light-emitting greenhouse film, which belongs to the field of polymer composite compositions. The preparation method comprises preparing manganese sulfate-treated montmorillonite, preparing organically modified hydrotalcite, preparing thermal insulation masterbatch, and preparing greenhouse film. The greenhouse film prepared by the present invention has excellent weather resistance. According to the method in GB / T4455-2019, the weather resistance of the film is tested, the exposure duration is set to 2200h, and the transverse fracture nominal strain retention rate of the film is 87.4-88.1%, and the longitudinal fracture nominal strain retention rate is 84.9-85.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a color-changing light-emitting greenhouse film, and belongs to the field of polymer compound compositions. Background Art

[0002] Agricultural plastic films are roughly divided into three categories according to their functional development, including ordinary plastic greenhouse films, functional plastic greenhouse films (including anti-aging, anti-fog, heat preservation and dust prevention, etc.), and controlled functional plastic greenhouse films (including spectrum selection, spectrum conversion, functional control, etc.). Among them, controlled functional plastic greenhouse films are the development hotspot in the 21st century, which is the need for the development of artificial environment greenhouses and the needs of modern agriculture.

[0003] Due to considerations of cost, lifespan and practicality, unlike electrically controlled dimming, greenhouse films are mainly dimmed through light conversion agents and inorganic scattering fillers. This is a passive, naturally adjusted dimming mechanism that adjusts the light at different times to suit the needs of crop growth. Domestic and foreign research and development of high-light-efficiency plastic greenhouse films can be summarized into two categories. The first category mainly uses the method of adding additives (such as adding rare earth materials or organic fluorescent materials) to produce light-converting plastic greenhouse films. The second category is based on the differences in spectral absorption of different polymers to design and produce multi-layer composite films, such as PE / EVA / PE, PE / PVC / PE, etc.

[0004] Rare earth inorganic compounds and rare earth organic compounds or organic conjugated molecular compounds are used, dispersed in a certain proportion in polyolefin compounds, and blown into film to produce fluorescence conversion, converting ultraviolet light into blue light and red light, and more directly turning green light that is useless for photosynthesis of most plants into red light. The central wavelength of the obtained fluorescence spectrum is more in line with the absorption spectrum of photosynthesis, which can greatly increase the photosynthesis rate, more effectively promote the growth, maturity, and yield of crops, and improve the quality of crops. However, due to the singleness of its light conversion function, the scattered light effect will not change with time and temperature, and the temperature regulation function in the greenhouse cannot be realized, resulting in the continuous high temperature in the greenhouse and burning the crops, or the low temperature in the greenhouse causing slow growth or frostbite of the crops.

[0005] In order to achieve the dimming function, the multi-layer greenhouse film in the existing technology can add inorganic fillers on one side of the inner film. Through a mechanism similar to that of frosted glass, the scattering degree of the product can be adjusted according to the changes in sunlight and the temperature and humidity in the greenhouse. In the morning and evening, the greenhouse film is closed, and the water vapor produced by plant transpiration adheres to the surface of the film and appears transparent, which increases the temperature in the greenhouse. After the high temperature at noon, the vents are opened, and the film surface in the greenhouse will slowly dry, increasing the haze value of the product. After passing through the product, the sunlight is scattered in the greenhouse and will not burn the crops. At the same time, the high temperature in the greenhouse is reduced, which improves crop growth.

[0006] In order to ensure the overall dimming performance of the film, the thickness of the inner film needs to be controlled within a smaller range. Taking the specifications of the five-layer blown film as the standard, the maximum thickness of the inner film should not be greater than 0.02mm. Since more inorganic fillers are distributed in the inner film, the weather resistance of the film will be poor. The longer the exposure time, the lower the nominal fracture strain of the film, and the lower the retention rate of the nominal fracture strain. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the defects of the prior art. Montmorillonite is treated with manganese sulfate and used as the raw material of the inner layer material. In combination with the thermal insulation masterbatch with organic modified hydrotalcite, greenhouse film is prepared. Under the premise of ensuring the dimming performance of the film, the weather resistance of the film is improved, especially the retention rate of the nominal strain at break is improved.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A method for preparing a color-changing light-emitting greenhouse film comprises preparing manganese sulfate-treated montmorillonite, preparing organically modified hydrotalcite, preparing heat-insulating masterbatch, and preparing the greenhouse film.

[0010] The following are further improvements to the above technical solution:

[0011] The method for preparing manganese sulfate treated montmorillonite is as follows: montmorillonite is mixed with deionized water, the stirring speed is controlled to be 75-125r / min, and the mixture is stirred until the montmorillonite is uniformly dispersed in the deionized water, and then the mixture is allowed to stand to allow the montmorillonite to hydrate and swell, and the standing time is 140-150min. After the standing time is completed, a montmorillonite slurry is obtained, and then an aqueous solution of manganese sulfate is added to the montmorillonite slurry, the stirring speed is controlled to be 125-175r / min, and the mixture is stirred for 55-65min. After the stirring is completed, a mixture is obtained, and the mixture is placed in an oven, the temperature is controlled to be 110-130°C, and the mixture is dried. When the mixture is dried to a water content of 15-20wt%, the mixture is taken out and placed in a muffle furnace, the heating speed is controlled to be 2.0-3.0°C / min, the temperature is raised to 465-485°C, and the calcination is performed for 220-260min. After the calcination is completed, the mixture is naturally cooled to room temperature to obtain manganese sulfate treated montmorillonite;

[0012] The mass ratio of the montmorillonite to deionized water is 1:9-11;

[0013] The montmorillonite has a particle size of 0.8 μm, a silicon dioxide content of 56.65 wt %, an iron oxide content of 6.71 wt %, and an aluminum oxide content of 16.64 wt %;

[0014] The mass ratio of the montmorillonite slurry to the aqueous solution of manganese sulfate is 15:6.5-7.5;

[0015] The concentration of the aqueous solution of manganese sulfate is 8-12 wt %.

[0016] The method for preparing the organic modified hydrotalcite comprises: mixing the hydrotalcite with dimethyl sulfoxide, stirring to make it dispersed evenly, obtaining a dispersion of the hydrotalcite, then adding coconut oil chloride to the dispersion of the hydrotalcite, controlling the temperature to 46-49° C., stirring for 13-18 minutes, and after the stirring is completed, keeping the temperature unchanged, adding triethylamine and imidazole in sequence, and continuing to stir for 125-175 minutes. After the stirring is completed, filtering, washing, and drying to obtain the organic modified hydrotalcite;

[0017] The mass ratio of the hydrotalcite to dimethyl sulfoxide is 1:7.5-8.5;

[0018] The hydrotalcite has a fineness of 500 mesh, an aluminum oxide content of 18.21wt%, and a magnesium oxide content of 33.57wt%;

[0019] The mass ratio of the hydrotalcite dispersion, coconut oil chloride, triethylamine and imidazole is 750-1250:45-75:4.5-5.5:0.17-0.23.

[0020] The method for preparing the thermal insulation masterbatch is to uniformly mix the linear low-density polyethylene, the organically modified hydrotalcite and the antioxidant, control the temperature to be 158-166° C., perform kneading for 55-65 minutes, and after the kneading is completed, extrude and granulate to obtain the thermal insulation masterbatch;

[0021] The mass ratio of the linear low-density polyethylene, the organically modified hydrotalcite, and the antioxidant is 70-80:22-28:1.9-2.1;

[0022] The density of the linear low-density polyethylene is 0.920 g / cm 3 ;

[0023] The model of the antioxidant is antioxidant 1076.

[0024] The method for preparing the greenhouse film comprises: uniformly mixing the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material respectively, adding them into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, setting the extrusion working temperature of the five extruders to 173-177° C., sequentially performing melting, mixing and plasticizing, and then extruding the plasticized materials in the five extruders into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruding them into a tubular shape through the die mouth, and then performing blow molding, cooling and winding to obtain a color-changing light-emitting greenhouse film;

[0025] The structure of the greenhouse film is five layers from top to bottom, namely outer layer, sub-outer layer, middle layer, sub-inner layer, and inner layer. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.03mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.03mm, and the thickness of the inner layer is 0.02mm. The total thickness of the color-changing light-emitting greenhouse film is 0.15mm.

[0026] The outer layer material comprises the following components by weight: 22-28 parts of low-density polyethylene, 45-55 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant;

[0027] The secondary outer layer material comprises the following components by weight: 32-38 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 32-38 parts of linear low-density polyethylene, 4.5-5.5 parts of light conversion agent, and 0.45-0.55 parts of antioxidant;

[0028] The middle layer material comprises the following components by weight: 22-28 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 22-28 parts of thermal insulation masterbatch, and 0.45-0.55 parts of antioxidant;

[0029] The secondary inner layer material comprises the following components by weight: 32-38 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 32-38 parts of linear low-density polyethylene, 13-17 parts of thermal insulation masterbatch, and 0.45-0.55 parts of antioxidant;

[0030] The inner layer material comprises the following components by weight: 13-17 parts of low-density polyethylene, 45-55 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 13-17 parts of manganese sulfate-treated montmorillonite, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant;

[0031] The model of the light-converting agent in the secondary outer layer material is Xiweier GTR650-Ⅰ (green to red);

[0032] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.913 g / cm 3 The density of metallocene linear low-density polyethylene is 0.929 g / cm 3 The density of linear low-density polyethylene is 0.920 g / cm 3 ;

[0033] The antioxidant model in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is hindered amine stabilizer, model light stabilizer XT100; the antioxidant in the outer layer material and the inner layer material is antioxidant 1076.

[0034] Compared with the prior art, the present invention achieves the following beneficial effects:

[0035] The greenhouse film prepared by the present invention has excellent mechanical properties. According to the method in GB / T4455-2019, the tensile strength, nominal strain at break, and right-angle tear strength of the film are tested. The transverse tensile strength is 35.2-36.1 MPa, the longitudinal tensile strength is 32.6-33.4 MPa, the transverse nominal strain at break is 947-975%, the longitudinal nominal strain at break is 854-882%, the transverse right-angle tear strength is 138-142 kN / m, and the longitudinal right-angle tear strength is 133-138 kN / m;

[0036] The greenhouse film prepared by the present invention has excellent weather resistance. According to the method in GB / T4455-2019, the weather resistance of the film is tested, and the exposure duration of the weather resistance test is set to 2200h. After the exposure is completed, the nominal strain retention rate at break, the tensile strength retention rate, and the tear strength retention rate of the film are tested and calculated. The transverse tensile strength retention rate is 89.8-90.5%, the longitudinal tensile strength retention rate is 87.6-90.3%, the transverse nominal strain retention rate at break is 87.4-88.1%, the longitudinal nominal strain retention rate at break is 84.9-85.5%, the transverse right-angle tear strength retention rate is 86.7-87.4%, and the longitudinal right-angle tear strength retention rate is 90.8-92.1%;

[0037] The greenhouse film prepared by the present invention has a relatively sensitive dimming performance. According to the method in GB / T4455-2019, the transparency and haze of the film are tested at different humidity. The relative humidity of the test environment is set to 20%, 50%, and 80%, respectively. When the relative humidity is 20%, the transparency of the film is 91.4-92.8%, when the relative humidity is 50%, the transparency of the film is 66.7-68.1%, and when the relative humidity is 80%, the transparency of the film is 51.4-53.1%; when the relative humidity is 20%, the haze of the film is 5.1-6.2%, when the relative humidity is 50%, the haze of the film is 28.8-30.2%, and when the relative humidity is 80%, the haze of the film is 44.8-46.0%;

[0038] The greenhouse film prepared by the present invention has strong infrared and ultraviolet shielding performance. The infrared blocking rate of the film is 63.85-65.5%, and the ultraviolet blocking rate is 85.8-87.2% when tested using an ultraviolet infrared blocking rate and a visible light transmittance tester.

[0039] The greenhouse film prepared by the present invention can effectively improve the photosynthesis of crops and appropriately reduce the transpiration of plants. On the 20th day of the growth cycle of Chinese cabbage, the photosynthetic rate and transpiration rate of the cabbage were tested at 8:00, 12:00 and 16:00 respectively using a portable photosynthesis meter. The photosynthetic rate at 8:00 was 29.74-30.51 μmol·m -2 s -1 The photosynthetic rate at 12:00 was 35.21-36.03 μmol·m -2 s -1 The photosynthetic rate at 16:00 was 27.86-28.55 μmol·m -2 s -1 ; The transpiration rate at 8:00 was 3.59-3.77mmol·m -2 s -1 The transpiration rate at 12:00 was 5.17-5.35mmol·m -2 s -1 The transpiration rate at 16:00 was 4.28-4.65mmol·m -2 s -1 . DETAILED DESCRIPTION

[0040] Example 1

[0041] (1) Preparation of manganese sulfate treated montmorillonite

[0042] Mix montmorillonite with deionized water, control the speed to 90r / min, stir until the montmorillonite is evenly dispersed in the deionized water, then let it stand to allow the montmorillonite to hydrate and swell, and let it stand for 145min. After the standing is completed, a montmorillonite slurry is obtained, and then an aqueous solution of manganese sulfate is added to the montmorillonite slurry, and the stirring speed is controlled to 150r / min, and the stirring time is 60min. After the stirring is completed, a mixture is obtained, and the mixture is placed in an oven, and the temperature is controlled to 120℃ for drying. After drying to a water content of 18wt%, take it out and place it in a muffle furnace, control the heating rate to 2.5℃ / min, and heat it to 475℃ for calcination. The calcination time is 240min. After the calcination is completed, it is naturally cooled to room temperature to obtain manganese sulfate-treated montmorillonite;

[0043] The mass ratio of the montmorillonite to deionized water is 1:10;

[0044] The montmorillonite has a particle size of 0.8 μm, a silicon dioxide content of 56.65 wt %, an iron oxide content of 6.71 wt %, and an aluminum oxide content of 16.64 wt %;

[0045] The mass ratio of the montmorillonite slurry to the aqueous solution of manganese sulfate is 15:7;

[0046] The concentration of the aqueous solution of manganese sulfate is 10 wt %.

[0047] (2) Preparation of organic modified hydrotalcite

[0048] The hydrotalcite and dimethyl sulfoxide are mixed and stirred to be uniformly dispersed to obtain a dispersion of the hydrotalcite, and then coconut oil chloride is added to the dispersion of the hydrotalcite, and the temperature is controlled to be 47° C. and stirred for 15 minutes. After the stirring is completed, the temperature is kept unchanged, triethylamine and imidazole are added in sequence, and the stirring is continued for 150 minutes. After the stirring is completed, the organically modified hydrotalcite is obtained by filtering, washing, and drying;

[0049] The mass ratio of the hydrotalcite to dimethyl sulfoxide is 1:8;

[0050] The hydrotalcite has a fineness of 500 mesh, an aluminum oxide content of 18.21wt%, and a magnesium oxide content of 33.57wt%;

[0051] The mass ratio of the hydrotalcite dispersion, coconut oil chloride, triethylamine and imidazole is 1000:60:5:0.2.

[0052] (3) Preparation of thermal insulation masterbatch

[0053] The linear low-density polyethylene, organically modified hydrotalcite and antioxidant were mixed uniformly, the temperature was controlled at 162°C, and the mixing time was 60 minutes. After the mixing was completed, the mixture was extruded and granulated to obtain a thermal insulation masterbatch;

[0054] The mass ratio of the linear low-density polyethylene, the organically modified hydrotalcite, and the antioxidant is 75:25:2;

[0055] The density of the linear low-density polyethylene is 0.920 g / cm 3 ;

[0056] The model of the antioxidant is antioxidant 1076.

[0057] (4) Preparation of greenhouse film

[0058] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 175° C., and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die, and then blown, cooled and rolled to obtain a color-changing light-emitting shed film;

[0059] The structure of the greenhouse film is five layers from top to bottom, namely outer layer, sub-outer layer, middle layer, sub-inner layer, and inner layer. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.03mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.03mm, and the thickness of the inner layer is 0.02mm. The total thickness of the color-changing light-emitting greenhouse film is 0.15mm.

[0060] The outer layer material comprises the following components by weight: 25 parts of low-density polyethylene, 50 parts of metallocene linear low-density polyethylene, 25 parts of linear low-density polyethylene, 0.8 parts of antioxidant, 0.8 parts of light stabilizer, and 0.5 parts of antioxidant;

[0061] The secondary outer layer material comprises the following components by weight: 35 parts of low-density polyethylene, 10 parts of metallocene linear low-density polyethylene, 35 parts of linear low-density polyethylene, 5 parts of light conversion agent, and 0.5 parts of antioxidant;

[0062] The middle layer material comprises the following components by weight: 25 parts of low-density polyethylene, 10 parts of metallocene linear low-density polyethylene, 25 parts of linear low-density polyethylene, 25 parts of thermal insulation masterbatch, and 0.5 parts of antioxidant;

[0063] The secondary inner layer material comprises the following components by weight: 35 parts of low-density polyethylene, 10 parts of metallocene linear low-density polyethylene, 35 parts of linear low-density polyethylene, 15 parts of thermal insulation masterbatch, and 0.5 parts of antioxidant;

[0064] The inner layer material comprises the following components by weight: 15 parts of low-density polyethylene, 50 parts of metallocene linear low-density polyethylene, 25 parts of linear low-density polyethylene, 15 parts of manganese sulfate-treated montmorillonite, 0.8 parts of antioxidant, 0.8 parts of light stabilizer, and 0.5 parts of antioxidant;

[0065] The model of the light-converting agent in the secondary outer layer material is Xiweier GTR650-Ⅰ (green to red);

[0066] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.913 g / cm 3 The density of metallocene linear low-density polyethylene is 0.929 g / cm 3 The density of linear low-density polyethylene is 0.920 g / cm 3 ;

[0067] The antioxidant model in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is hindered amine stabilizer, model light stabilizer XT100; the antioxidant in the outer layer material and the inner layer material is antioxidant 1076. Example 2

[0068] (1) Preparation of manganese sulfate treated montmorillonite

[0069] Mix montmorillonite with deionized water, control the speed to 75r / min, stir until the montmorillonite is evenly dispersed in the deionized water, then let it stand to allow the montmorillonite to hydrate and swell, and let it stand for 150 minutes. After the standing is completed, a montmorillonite slurry is obtained, and then an aqueous solution of manganese sulfate is added to the montmorillonite slurry, and the stirring speed is controlled to 125r / min, and the stirring time is 65 minutes. After the stirring is completed, a mixture is obtained, and the mixture is placed in an oven, and the temperature is controlled to 110°C for drying. After drying to a water content of 15wt%, take it out and place it in a muffle furnace, control the heating rate to 2.0°C / min, and heat it to 485°C for calcination. The calcination time is 220 minutes. After the calcination is completed, it is naturally cooled to room temperature to obtain manganese sulfate-treated montmorillonite;

[0070] The mass ratio of the montmorillonite to deionized water is 1:9;

[0071] The montmorillonite has a particle size of 0.8 μm, a silicon dioxide content of 56.65 wt %, an iron oxide content of 6.71 wt %, and an aluminum oxide content of 16.64 wt %;

[0072] The mass ratio of the montmorillonite slurry to the aqueous solution of manganese sulfate is 15:6.5;

[0073] The concentration of the aqueous solution of manganese sulfate is 8 wt %.

[0074] (2) Preparation of organic modified hydrotalcite

[0075] The hydrotalcite and dimethyl sulfoxide are mixed and stirred to be uniformly dispersed to obtain a dispersion of the hydrotalcite, and then coconut oil chloride is added to the dispersion of the hydrotalcite, and the temperature is controlled to be 46° C. and stirred for 18 minutes. After the stirring is completed, the temperature is kept unchanged, triethylamine and imidazole are added in sequence, and the stirring is continued for 125 minutes. After the stirring is completed, the organically modified hydrotalcite is obtained by filtering, washing, and drying;

[0076] The mass ratio of the hydrotalcite to dimethyl sulfoxide is 1:7.5;

[0077] The hydrotalcite has a fineness of 500 mesh, an aluminum oxide content of 18.21wt%, and a magnesium oxide content of 33.57wt%;

[0078] The mass ratio of the hydrotalcite dispersion, coconut oil chloride, triethylamine and imidazole is 750:45:4.5:0.17.

[0079] (3) Preparation of thermal insulation masterbatch

[0080] The linear low-density polyethylene, organically modified hydrotalcite and antioxidant were mixed uniformly, the temperature was controlled at 158°C, the mixing time was 65 minutes, and after the mixing was completed, extrusion granulation was performed to obtain a thermal insulation masterbatch;

[0081] The mass ratio of the linear low-density polyethylene, the organically modified hydrotalcite, and the antioxidant is 70:22:1.9;

[0082] The density of the linear low-density polyethylene is 0.920 g / cm 3 ;

[0083] The model of the antioxidant is antioxidant 1076.

[0084] (4) Preparation of greenhouse film

[0085] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 173° C., and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die, and then blown, cooled and rolled to obtain a color-changing light-emitting shed film;

[0086] The structure of the greenhouse film is five layers from top to bottom, namely outer layer, sub-outer layer, middle layer, sub-inner layer, and inner layer. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.03mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.03mm, and the thickness of the inner layer is 0.02mm. The total thickness of the color-changing light-emitting greenhouse film is 0.15mm.

[0087] The outer layer material comprises the following components by weight: 22 parts of low-density polyethylene, 45 parts of metallocene linear low-density polyethylene, 22 parts of linear low-density polyethylene, 0.7 parts of antioxidant, 0.7 parts of light stabilizer, and 0.45 parts of antioxidant;

[0088] The secondary outer layer material comprises the following components by weight: 32 parts of low-density polyethylene, 8 parts of metallocene linear low-density polyethylene, 32 parts of linear low-density polyethylene, 4.5 parts of light conversion agent, and 0.45 parts of antioxidant;

[0089] The middle layer material comprises the following components by weight: 22 parts of low-density polyethylene, 8 parts of metallocene linear low-density polyethylene, 22 parts of linear low-density polyethylene, 22 parts of thermal insulation masterbatch, and 0.45 parts of antioxidant;

[0090] The secondary inner layer material comprises the following components by weight: 32 parts of low-density polyethylene, 8 parts of metallocene linear low-density polyethylene, 32 parts of linear low-density polyethylene, 13 parts of thermal insulation masterbatch, and 0.45 parts of antioxidant;

[0091] The inner layer material comprises the following components by weight: 13 parts of low-density polyethylene, 45 parts of metallocene linear low-density polyethylene, 22 parts of linear low-density polyethylene, 13 parts of manganese sulfate-treated montmorillonite, 0.7 parts of antioxidant, 0.7 parts of light stabilizer, and 0.45 parts of antioxidant;

[0092] The model of the light-converting agent in the secondary outer layer material is Xiweier GTR650-Ⅰ (green to red);

[0093] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.913 g / cm 3 The density of metallocene linear low-density polyethylene is 0.929 g / cm 3 The density of linear low-density polyethylene is 0.920 g / cm 3 ;

[0094] The antioxidant model in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is hindered amine stabilizer, model light stabilizer XT100; the antioxidant in the outer layer material and the inner layer material is antioxidant 1076. Example 3

[0095] (1) Preparation of manganese sulfate treated montmorillonite

[0096] Mix montmorillonite with deionized water, control the speed to 125r / min, stir until the montmorillonite is evenly dispersed in the deionized water, then let it stand to allow the montmorillonite to hydrate and swell, and let it stand for 140 minutes. After the standing is completed, a montmorillonite slurry is obtained, and then an aqueous solution of manganese sulfate is added to the montmorillonite slurry, and the stirring speed is controlled to 175r / min, and the stirring time is 55 minutes. After the stirring is completed, a mixture is obtained, and the mixture is placed in an oven, and the temperature is controlled to 130°C for drying. After drying to a water content of 20wt%, take it out and place it in a muffle furnace, control the heating rate to 3.0℃ / min, and heat it to 465℃ for calcination. The calcination time is 260min. After the calcination is completed, it is naturally cooled to room temperature to obtain manganese sulfate-treated montmorillonite;

[0097] The mass ratio of the montmorillonite to deionized water is 1:11;

[0098] The montmorillonite has a particle size of 0.8 μm, a silicon dioxide content of 56.65 wt %, an iron oxide content of 6.71 wt %, and an aluminum oxide content of 16.64 wt %;

[0099] The mass ratio of the montmorillonite slurry to the aqueous solution of manganese sulfate is 15:7.5;

[0100] The concentration of the aqueous solution of manganese sulfate is 12 wt %.

[0101] (2) Preparation of organic modified hydrotalcite

[0102] The hydrotalcite and dimethyl sulfoxide are mixed and stirred to be uniformly dispersed to obtain a dispersion of the hydrotalcite, and then coconut oil chloride is added to the dispersion of the hydrotalcite, and the temperature is controlled to be 49° C. and stirred for 13 minutes. After the stirring is completed, the temperature is kept unchanged, triethylamine and imidazole are added in sequence, and the stirring is continued for 175 minutes. After the stirring is completed, the organically modified hydrotalcite is obtained by filtering, washing, and drying;

[0103] The mass ratio of the hydrotalcite to dimethyl sulfoxide is 1:8.5;

[0104] The hydrotalcite has a fineness of 500 mesh, an aluminum oxide content of 18.21wt%, and a magnesium oxide content of 33.57wt%;

[0105] The mass ratio of the hydrotalcite dispersion, coconut oil chloride, triethylamine and imidazole is 1250:75:5.5:0.23.

[0106] (3) Preparation of thermal insulation masterbatch

[0107] The linear low-density polyethylene, organically modified hydrotalcite and antioxidant were mixed uniformly, the temperature was controlled at 166°C, and the mixing time was 55 minutes. After the mixing was completed, the mixture was extruded and granulated to obtain a thermal insulation masterbatch;

[0108] The mass ratio of the linear low-density polyethylene, the organically modified hydrotalcite, and the antioxidant is 80:28:2.1;

[0109] The density of the linear low-density polyethylene is 0.920 g / cm 3 ;

[0110] The model of the antioxidant is antioxidant 1076.

[0111] (4) Preparation of greenhouse film

[0112] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 177° C., and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die, and then blown, cooled and rolled to obtain a color-changing light-emitting shed film;

[0113] The structure of the greenhouse film is five layers from top to bottom, namely outer layer, sub-outer layer, middle layer, sub-inner layer, and inner layer. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.03mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.03mm, and the thickness of the inner layer is 0.02mm. The total thickness of the color-changing light-emitting greenhouse film is 0.15mm.

[0114] The outer layer material comprises the following components by weight: 28 parts of low-density polyethylene, 55 parts of metallocene linear low-density polyethylene, 28 parts of linear low-density polyethylene, 0.9 parts of antioxidant, 0.9 parts of light stabilizer, and 0.55 parts of antioxidant;

[0115] The secondary outer layer material comprises the following components by weight: 38 parts of low-density polyethylene, 12 parts of metallocene linear low-density polyethylene, 38 parts of linear low-density polyethylene, 5.5 parts of light conversion agent, and 0.55 parts of antioxidant;

[0116] The middle layer material comprises the following components by weight: 28 parts of low-density polyethylene, 12 parts of metallocene linear low-density polyethylene, 28 parts of linear low-density polyethylene, 28 parts of thermal insulation masterbatch, and 0.55 parts of antioxidant;

[0117] The secondary inner layer material comprises the following components by weight: 38 parts of low-density polyethylene, 12 parts of metallocene linear low-density polyethylene, 38 parts of linear low-density polyethylene, 17 parts of thermal insulation masterbatch, and 0.55 parts of antioxidant;

[0118] The inner layer material comprises the following components by weight: 17 parts of low-density polyethylene, 55 parts of metallocene linear low-density polyethylene, 28 parts of linear low-density polyethylene, 17 parts of manganese sulfate-treated montmorillonite, 0.9 parts of antioxidant, 0.9 parts of light stabilizer, and 0.55 parts of antioxidant;

[0119] The model of the light-converting agent in the secondary outer layer material is Xiweier GTR650-Ⅰ (green to red);

[0120] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.913 g / cm 3 The density of metallocene linear low-density polyethylene is 0.929 g / cm 3 The density of linear low-density polyethylene is 0.920 g / cm 3 ;

[0121] The antioxidant model in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is hindered amine stabilizer, model light stabilizer XT100; the antioxidant in the outer layer material and the inner layer material is antioxidant 1076.

[0122] Comparative Example 1

[0123] The difference from Example 1 is that the step of preparing montmorillonite treated with manganese sulfate is omitted, and untreated montmorillonite is used as the raw material component of the inner layer material, and the dosage is kept unchanged. The remaining steps are the same to prepare the membrane;

[0124] The montmorillonite has a particle size of 0.8 μm, a silicon dioxide content of 56.65 wt %, an iron oxide content of 6.71 wt %, and an aluminum oxide content of 16.64 wt %.

[0125] Comparative Example 2

[0126] The difference from Example 1 is that the step of preparing the organically modified hydrotalcite is omitted, and the thermal insulation masterbatch is prepared by using the untreated hydrotalcite while keeping the dosage unchanged, and the remaining steps are the same to prepare the film;

[0127] The hydrotalcite has a fineness of 500 mesh, an aluminum oxide content of 18.21 wt %, and a magnesium oxide content of 33.57 wt %.

[0128] Test Example 1 Mechanical properties test of membrane

[0129] The films of Examples 1-3 and Comparative Examples 1-2 were tested for tensile strength, nominal strain at break, and right-angle tear strength according to the method in GB / T4455-2019. The results are shown in Table 1.

[0130] Table 1

[0131]

[0132] In Example 1-3, montmorillonite was treated with manganese sulfate and used as the raw material of the inner layer material. In combination with the addition of an organically modified hydrotalcite thermal insulation masterbatch, the greenhouse film was prepared. The mechanical properties of the greenhouse film were relatively high.

[0133] Comparative Example 1 omitted the step of preparing manganese sulfate treated montmorillonite and used untreated montmorillonite as the raw material component of the inner layer material, which caused the mechanical properties of the film to decrease, especially the decrease in the nominal strain at break was particularly serious, and the tensile strength and right-angle tear strength also decreased to a certain extent;

[0134] Comparative Example 2 omits the step of preparing organically modified hydrotalcite and uses untreated hydrotalcite to prepare thermal insulation masterbatch, which causes a decrease in the mechanical properties of the film, especially the tensile strength and right-angle tear strength. In addition, the nominal strain at break also decreases to a certain extent.

[0135] Test Example 2 Weathering Test of Film

[0136] The weather resistance of the films of Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T4455-2019. The exposure duration of the weather resistance test was set to 2200 h. After the exposure was completed, the nominal strain retention rate at break, the tensile strength retention rate, and the tear strength retention rate of the films were tested and calculated. The results are shown in Table 2.

[0137] Table 2

[0138]

[0139] In Example 1-3, montmorillonite was treated with manganese sulfate and used as the raw material of the inner layer material. In combination with the thermal insulation masterbatch containing organic modified hydrotalcite, the greenhouse film was prepared. The greenhouse film had good weather resistance, and the retention rate of nominal strain at crack, the retention rate of tensile strength, and the retention rate of tear strength were all high.

[0140] Comparative Example 1 omitted the step of preparing manganese sulfate treated montmorillonite and used untreated montmorillonite as the raw material component of the inner layer material, which caused the weather resistance of the film to decrease, especially the decrease of the nominal strain retention rate at break and the right-angle tear strength retention rate, and the tensile strength retention rate also decreased to a certain extent;

[0141] Comparative Example 2 omits the step of preparing organically modified hydrotalcite and uses untreated hydrotalcite to prepare thermal insulation masterbatch, which will cause the weather resistance of the film to decrease, especially the tensile strength retention rate to decrease particularly seriously. In addition, the nominal strain retention rate at break and the right-angle tear strength retention rate also decrease to a certain extent.

[0142] Test Example 3: Film dimming performance test

[0143] The films of Examples 1-3 and Comparative Examples 1-2 were tested for transparency and haze at different humidity levels according to the method in GB / T4455-2019. The relative humidity of the test environment was set to 20%, 50%, and 80%, respectively. The results are shown in Table 3.

[0144] Table 3

[0145]

[0146] In Example 1-3, montmorillonite was treated with manganese sulfate and used as the raw material of the inner layer material. In combination with the thermal insulation masterbatch containing organically modified hydrotalcite, the greenhouse film was prepared. The dimming performance of the greenhouse film was relatively sensitive. When the relative humidity was high, the transparency of the film would be significantly reduced, and the haze would be significantly increased.

[0147] Comparative Example 1 omitted the step of preparing manganese sulfate treated montmorillonite and used untreated montmorillonite as the raw material component of the inner layer material, which caused the dimming performance of the film to decrease. When the relative humidity of the environment increased, the transparency could not be effectively reduced, and the haze increased less.

[0148] Comparative Example 2 omits the step of preparing organically modified hydrotalcite and uses untreated hydrotalcite to prepare thermal insulation masterbatch, which causes the dimming performance of the film to decrease. When the relative humidity of the environment increases, the transparency cannot be effectively reduced and the increase in haze is also small.

[0149] Test Example 4 Film infrared and ultraviolet shielding performance test

[0150] The films prepared in Examples 1-3 and Comparative Examples 1-2 were tested for average infrared blocking rate and average ultraviolet blocking rate using an LS182 ultraviolet infrared blocking rate and visible light transmittance tester. The results are shown in Table 4.

[0151] Table 4

[0152]

[0153] In Example 1-3, montmorillonite treated with manganese sulfate was used as the raw material of the inner layer material, and the greenhouse film was prepared by adding a thermal insulation masterbatch of organically modified hydrotalcite. The greenhouse film has good infrared and ultraviolet shielding properties and a high infrared and ultraviolet blocking rate.

[0154] Comparative Example 1 omitted the step of preparing manganese sulfate treated montmorillonite and used untreated montmorillonite as the raw material component of the inner layer material, which caused the infrared and ultraviolet shielding performance of the film to decrease, especially the infrared blocking rate to decrease more seriously, and the ultraviolet blocking rate also decreased to a certain extent;

[0155] Comparative Example 2 omits the step of preparing organically modified hydrotalcite and uses untreated hydrotalcite to prepare thermal insulation masterbatch, which causes the infrared and ultraviolet shielding performance of the film to decrease, especially the ultraviolet blocking rate to decrease more seriously. In addition, the infrared blocking rate also decreases to a certain extent.

[0156] Test Example 5: Test on the impact on plant photosynthesis

[0157] The films prepared in Examples 1-3 and Comparative Examples 1-2 were applied to the cultivation of pakchoi. On the 20th day of the growth cycle of the pakchoi, the photosynthetic rate and transpiration rate were tested at 8:00, 12:00 and 16:00, respectively. The test method was instrumental testing, using a CI-30PLS portable photosynthesis meter. The test time was mid-April, and the monthly average temperature was 14°C. The results are shown in Table 5.

[0158] Table 5

[0159]

[0160] Example 1-3 uses manganese sulfate to treat montmorillonite, uses it as the raw material of the inner layer material, and combines it with the thermal insulation masterbatch of organic modified hydrotalcite to prepare greenhouse film, which can effectively increase the photosynthetic rate of crops at different times and reduce the transpiration rate of crops;

[0161] In Comparative Example 1, the step of preparing manganese sulfate-treated montmorillonite was omitted, and untreated montmorillonite was used as the raw material component of the inner layer material. The prepared greenhouse film had a poor effect on improving the photosynthetic rate of plants, and at the same time, had a poor effect on reducing the transpiration rate of plants, which would affect the growth of plants and the accumulation of nutrients;

[0162] Comparative Example 2 omits the step of preparing organically modified hydrotalcite and uses untreated hydrotalcite to prepare thermal insulation masterbatch. The prepared greenhouse film has poor effect on improving the photosynthetic rate of plants and poor effect on reducing the transpiration rate of plants, which will affect the growth of plants and the accumulation of nutrients.

Claims

1. A method for preparing a color-changing shed film, characterized in that: The preparation method comprises preparing manganese sulfate treated montmorillonite, preparing organic modified hydrotalcite, preparing thermal insulation masterbatch, and preparing greenhouse film; The method for preparing manganese sulfate treated montmorillonite comprises: mixing montmorillonite with deionized water, controlling the stirring speed to be 75-125 r / min, stirring until the montmorillonite is uniformly dispersed in the deionized water, and then standing to allow the montmorillonite to hydrate and swell, the standing time being 140-150 min, and obtaining a montmorillonite slurry after the standing is completed, and then adding an aqueous solution of manganese sulfate to the montmorillonite slurry, controlling the stirring speed to be 125-175 r / min, stirring, and the stirring time being 55-65 min, and obtaining a mixture after the stirring is completed, placing the mixture in an oven, controlling the temperature to be 110-130° C., and drying, and drying until the water content of the mixture is 15-20wt%, taking it out and placing it in a muffle furnace, controlling the heating speed to be 2.0-3.0° C. / min, heating to 465-485° C., and calcining, the calcining time being 220-260 min, and naturally cooling to room temperature after the calcination is completed, and obtaining manganese sulfate treated montmorillonite; The mass ratio of the montmorillonite to deionized water is 1:9-11; The mass ratio of the montmorillonite slurry to the aqueous solution of manganese sulfate is 15:6.5-7.5; The concentration of the aqueous solution of manganese sulfate is 8-12wt%; The method for preparing the organic modified hydrotalcite comprises: mixing the hydrotalcite with dimethyl sulfoxide, stirring to make it dispersed evenly, obtaining a dispersion of the hydrotalcite, then adding coconut oil chloride to the dispersion of the hydrotalcite, controlling the temperature to 46-49° C., stirring for 13-18 minutes, and after the stirring is completed, keeping the temperature unchanged, adding triethylamine and imidazole in sequence, and continuing to stir for 125-175 minutes. After the stirring is completed, filtering, washing, and drying to obtain the organic modified hydrotalcite; The mass ratio of the hydrotalcite to dimethyl sulfoxide is 1:7.5-8.5; The mass ratio of the hydrotalcite dispersion, coconut oil chloride, triethylamine and imidazole is 750-1250:45-75:4.5-5.5:0.17-0.23; The method for preparing the thermal insulation masterbatch is to uniformly mix the linear low-density polyethylene, the organically modified hydrotalcite and the antioxidant, control the temperature to be 158-166° C., perform kneading for 55-65 minutes, and after the kneading is completed, extrude and granulate to obtain the thermal insulation masterbatch; The mass ratio of the linear low-density polyethylene, the organically modified hydrotalcite, and the antioxidant is 70-80:22-28:1.9-2.1; The density of the linear low-density polyethylene is 0.920 g / cm 3 ; The method for preparing the greenhouse film comprises: uniformly mixing the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material respectively, adding them into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, setting the extrusion temperature to 173-177° C., sequentially performing melting, mixing and plasticizing, and then extruding the plasticized materials in the five extruders into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruding them into a tubular shape through the die mouth, and then performing blow molding, cooling and winding to obtain a color-changing light-emitting greenhouse film; The outer layer material comprises the following components by weight: 22-28 parts of low-density polyethylene, 45-55 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant; The secondary outer layer material comprises the following components by weight: 32-38 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 32-38 parts of linear low-density polyethylene, 4.5-5.5 parts of light conversion agent, and 0.45-0.55 parts of antioxidant; The middle layer material comprises the following components by weight: 22-28 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 22-28 parts of thermal insulation masterbatch, and 0.45-0.55 parts of antioxidant; The secondary inner layer material comprises the following components by weight: 32-38 parts of low-density polyethylene, 8-12 parts of metallocene linear low-density polyethylene, 32-38 parts of linear low-density polyethylene, 13-17 parts of thermal insulation masterbatch, and 0.45-0.55 parts of antioxidant; The inner layer material comprises the following components by weight: 13-17 parts of low-density polyethylene, 45-55 parts of metallocene linear low-density polyethylene, 22-28 parts of linear low-density polyethylene, 13-17 parts of manganese sulfate-treated montmorillonite, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant; The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.913 g / cm 3 The density of metallocene linear low-density polyethylene is 0.929 g / cm 3 The density of linear low-density polyethylene is 0.920 g / cm 3 .

2. The method for preparing a color-changing shed film according to claim 1, characterized in that: In the step of preparing manganese sulfate treated montmorillonite, the particle size of the montmorillonite is 0.8 μm, the silicon dioxide content is 56.65 wt %, the iron oxide content is 6.71 wt %, and the aluminum oxide content is 16.64 wt %.

3. The method for preparing a color-changing shed film according to claim 1, characterized in that: In the step of preparing the organic modified hydrotalcite, the fineness of the hydrotalcite is 500 mesh, the aluminum oxide content is 18.21 wt %, and the magnesium oxide content is 33.57 wt %.

4. The method for preparing a color-changing shed film according to claim 1, characterized in that: In the step of preparing the thermal insulation masterbatch, the model of the antioxidant is antioxidant 1076.

5. The method for preparing a color-changing shed film according to claim 1, characterized in that: The structure of the greenhouse film is a five-layer structure from top to bottom, namely outer layer, sub-outer layer, middle layer, sub-inner layer, and inner layer. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.03mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.03mm, the thickness of the inner layer is 0.02mm, and the total thickness of the color-changing light-emitting greenhouse film is 0.15mm.

6. The method for preparing a color-changing shed film according to claim 1, characterized in that: In the steps of preparing the greenhouse film, the model of the light transfer agent in the sub-outer layer material is Xiweier GTR650-Ⅰ; the model of the antioxidant in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material, and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is a hindered amine stabilizer, model XT100; the antioxidant in the outer layer material and the inner layer material is antioxidant 1076.

Citation Information

Patent Citations

  • Refractive index-matched additives for photo-curable compositions

    CN109791373A

  • Manganese-based montmorillonite low-temperature SCR catalyst and preparation method thereof

    CN110721674A